Evaluation of energy efficiency using thermodynamics analysis in a hydropower plant: A case study - Kahraman, Gokhan; Yucel, Halit Lutfi; Öztop, Hakan Fehmi (Pergamon-Elsevier Science Ltd, 2009)
In this study, efficiency evaluation for Keban hydropower plant (KHPP), located in Elazig-Turkey, was performed both experimentally and numerically by using thermodynamic analysis. Turbine efficiency was measured with direct method by measuring temperature of turbine inlet and outlet. Theoretical analysis was performed using a computer code and employing the experimental data. A good agreement between the calculated and measured values was observed. The study shows that using thermodynamic method for determination of turbine efficiency is an effective and easy method in a hydraulic power plant. (c) 2008 Elsevier Ltd. All rights reserved.
Keywords: Renewable energy; Hydraulic power plant; Thermodynamics; Turbine efficiency